Utilizing Craft Techniques in Zero Waste Fashion Design Clothing - Shella Wardhani Putri; Faradillah Nursari (Universitas Negeri Medan, 2023)
The role of research in design is to develop the potential that drives the creation of novel value in design. In the research process for design, the majority of designer-students have difficulties in determining the starting point or initial idea of a design, so they have the potential not to have a train of thought regarding what needs to be done in realizing the design and do not know the next process. One aspect that can enrich design ideas and novelty in fashion products is the application of craft techniques. With the application of craft techniques, the data and facts obtained become increasingly massive. So that the series of ideas-research-design requires a clear mapping of the flow of thinking in the creative process. Today's student-designers cannot be limited to just one research method, knowing that conceptual ideas can start from anywhere, such as design concept ideas that start from craft techniques in a linear mapping flow. This can be a reference regarding the linear flow of ideas-research-design that is carried out in zero waste fashion design to find out its potential, especially in the application of craft techniques. This research was conducted qualitatively by reviewing literature data and looking at examples of case studies from the student-designer work process using the linear method. Observations are made periodically for students who have designed the application of craft techniques to zero waste fashion design, to become research subjects and find out their creative process. The result of this study is an analysis of fashion product design methods with the application of craft techniques that have been carried out in a linear way of thinking as a reference for designers in producing innovative works.